Defining the link between peripheral neuronal activity and neuropathic pain: observational study protocol to investigate in vivo neurophysiological properties of nociceptors in patients with chronic neuropathic pain - Andreas C. Themistocleous; Georgios Baskozos; David L. H. Bennet; Jordi Serra (PLoS ONE, 2026)
Introduction Neuropathic pain affects up to 10% of the population and remains difficult to diagnose and treat effectively. Peripheral nociceptor hyperexcitability is thought to drive pain in a substantial subset of patients, yet human studies have not fully defined which nociceptor populations are abnormal or how these abnormalities relate to clinical phenotype, sensory profiling, or genetic mechanisms. Microneurography uniquely enables direct in vivo recording from human C-fibres, offering a mechanistic approach to patient stratification. This observational study investigates the relationships between neuropathic pain, nociceptor excitability, somatosensory phenotype, and genetic variation. Methods and analysis We will conduct an observational controlled study at the University of Oxford (2022–2029) following STROBE guidelines. Adults with and without neuropathy or neuropathic pain will undergo deep phenotyping, including questionnaires, neurological examination, quantitative sensory testing, nerve conduction studies, microneurography, skin biopsy, and genetic and transcriptomic analyses. Microneurography recordings will quantify C-fibre axonal properties, excitability, spontaneous activity, and responses to electrical, thermal, and mechanical stimulation. Participants will be stratified by neuropathy grade, neuropathic pain status, somatosensory phenotype, and genetic variants. Primary analyses will compare axonal excitability and related microneurography measures between participants with and without neuropathic pain. Secondary analyses will evaluate the associations between microneurography-derived nociceptor functional profiles and quantitative sensory phenotypes, and will assess the impact of rare ion-channel variants on C-fibre excitability. Multivariable regression, dimensionality reduction, and unsupervised clustering methods will be applied to delineate mechanistically informed patient subgroups. Ethics and dissemination Ethical approval was obtained from the South Central – Oxford C Research Ethics Committee (18/SC/0263). All participants will provide informed consent. Findings will be disseminated through peer-reviewed publications, conference presentations, and data-sharing compliant with institutional and funding-body policies. Strengths and limitations of this study The study uses microneurography, the only technique that directly records from human nociceptors in vivo, enabling detailed mechanistic assessment of C-fibre function. A deep phenotyping framework, including quantitative sensory testing, skin biopsy, nerve conduction studies, and genetic analysis, allows multidomain integration of clinical, neurophysiological, and molecular data. Classification of C-fibre subtypes using activity-dependent slowing provides a reproducible method to distinguish functional nociceptor populations. Extended microneurography protocols may not be feasible for all participants due to tolerability or signal instability, potentially reducing completeness of some secondary measures. As an observational study, causal inference is limited, and confounding will require careful adjustment despite prespecified statistical analyses.